2012
DOI: 10.1159/000337918
|View full text |Cite
|
Sign up to set email alerts
|

5/6 Nephrectomy as a Validated Rat Model Mimicking Human Warfarin-Related Nephropathy

Abstract: Background/Aims: We previously reported that patients with chronic kidney disease (CKD) receiving warfarin therapy and whose international normalized ratio increases to >3.0 may develop acute kidney injury (AKI) as a result of glomerular hemorrhage and formation of obstructive red blood cell (RBC) casts. We named this condition warfarin-related nephropathy (WRN). We also previously reported that acute excessive anticoagulation with brodifacoum (superwarfarin) induces AKI in 5/6 nephrectomy (5/6NE) rats. Limita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
103
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(109 citation statements)
references
References 15 publications
(26 reference statements)
6
103
0
Order By: Relevance
“…We used 5/6 nephrectomy rats 3 wk after the ablative surgery for these studies. Earlier we reported that the changes in serum creatinine and kidney morphology associated with anticoagulation were more prominent in 5/6 nephrectomy rats at 3 wk than at 9 and 19 wk after the ablative surgery (31).…”
Section: Resultsmentioning
confidence: 69%
See 4 more Smart Citations
“…We used 5/6 nephrectomy rats 3 wk after the ablative surgery for these studies. Earlier we reported that the changes in serum creatinine and kidney morphology associated with anticoagulation were more prominent in 5/6 nephrectomy rats at 3 wk than at 9 and 19 wk after the ablative surgery (31).…”
Section: Resultsmentioning
confidence: 69%
“…The 5/6 nephrectomy surgery was performed under a ketamine/xylazine (6.0 mg/0.77 mg/100 g) anesthesia by a nephrectomy of the right kidney and resection of twothirds of the left kidney (31,41). Animals were allowed to recover from the surgery for 3 wk before the start of warfarin treatment.. Warfarin and NAC were given per os in drinking water in the concentrations described below.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations